Adapting an Infectious Diseases Course for “Engaged Citizen” Themes - David S. Senchina (American Society for Microbiology, 2016)
This article describes philosophies and perspectives underpinning scientific citizenship–focused curricular changes implemented into a pre-existing undergraduate infectious diseases course. Impetus for the curricular changes was a novel, campus-wide, multidisciplinary “Engaged Citizen” theme for the general education curriculum. The first half of the article describes the larger contexts from which the curricular changes were borne and the resulting instructional model. The second half of the article shares both student and instructor perspectives on the curricular changes and potential application of the model to other science courses.